Assessment on dioxin-like compounds intake from various marine fish from Zhoushan Fishery, China. (January 2015) - Wang, Xiangyong; Zhang, Hongxia; Zhang, Lei; Zhong, Kai; Shang, Xiaohong; Zhao, Yunfeng; Tong, Zhendong; Yu, Xinwei; Li, Jingguang; Wu, Yongning
Highlights: 32 Fish species were measure for 29 dioxin-like compounds. The factors effecting the accumulation of the compounds in sea fish were discussed. A risk-based consumption advice for sea fish was developed. Abstract: Sea fish consuming is an important intake source of dioxin-like compounds, especially for the coastal residents. To assess the intake levels of these contaminants from sea fish and to provide risk-based consumption advice, concentrations of 17 polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) and 12 dioxin-like polychlorinated biphenyls (dl-PCBs) were measured in 32 commonly consumed fish species from Zhoushan Fishery, China. Due to the different accumulation influenced by fat content, feed habits and living zone in the sea area, the levels of PCDDs, PCDFs and dl-PCBs in different fish species varied significantly ranging from 0.002 to 0.078 pg WHO-TEQ/g fresh weight, from 0.002 to 0.553 pg WHO-TEQ/g fresh weight and from 0.003 to 2.059 pg WHO-TEQ/g fresh weight, respectively. Based on mean fish consuming rate in China, the estimated maximum possible dioxin-like compounds intake through different fish species ranged from 0.26 to 65.61 pg TEQ kg −1  bw month −1 . Bullet mackerel has the highest monthly intake level which was much higher than other fish species and very close to the provisional tolerable monthly intake (70 pg TEQ kg − 1  bw month − 1 ) proposed by the Joint FAO/WHO Expert Committee on Food Additives. Hence, comparing to other fish species, the consumption of Bullet mackerel from Zhoushan Fishery should be cautious to reduce the potential health risk.